Opioid Use and Appropriateness of Supply After Total Knee or Hip Arthroplasty: An Australian Perspective. Issue 23 (1st December 2020) - Tran, Tim; Castello, Jacinta; Taylor, Simone E.; Hardidge, Andrew; Cannizzaro, Shakara; George, Johnson; Elliott, Rohan A.
Abstract : Introduction: Effective pain management after joint arthroplasty is essential for optimal participation in rehabilitation. However, this needs to be balanced with potential risks associated with opioid use and community exposure. The aim of this study was to evaluate opioid use and appropriateness of supply on discharge after total knee arthroplasty or total hip arthroplasty at a major Australian health service. Methods: A prospective observational study was undertaken at an Australian 980-bed metropolitan health service. Patient interviews were conducted 3 weeks after hospital discharge to evaluate analgesic management and functional outcomes. The primary end point was the number of hospital-supplied opioid pills remaining 3 weeks postdischarge. Secondary end points included (1) factors associated with opioid use 3 weeks postdischarge, (2) opioid use in patients with poor functional outcomes, and (3) proportion of opioid naive patients who became chronic opioid users. Results: One hundred forty patients were included, and 137 were supplied opioids on discharge. At 3 weeks postdischarge, the median number of opioid pills remaining was 0 (interquartile range 0 to 8). There were 77 patients (56.2%) still taking opioids; surgery type, opioid use before admission, and the number of "as required" doses used 24 hours before discharge were independent predictors of opioid continuation. Patients with poor functional outcomes were supplied with more opioids on discharge, often not satisfied with the quantity supplied and more likely to be taking opioids 3 weeks postdischarge. There were 5 of 93 opioid naive patients (5.3%) who developed chronic opioid usage. Discussion: More than half of the patients undergoing total knee arthroplasty or total hip arthroplasty were still using opioids at 3 weeks postdischarge. Most patients were not supplied with excessive quantities at discharge. Future research should focus on identifying patients at risk of prolonged opioid use and improving the transition of these patients into the community. Level of Evidence: Level II—Prognostic study = prospective observational study.